2022
DOI: 10.1097/md.0000000000028514
|View full text |Cite
|
Sign up to set email alerts
|

LigaSure hemorrhoidectomy versus the procedure for prolapse and hemorrhoids

Abstract: Background: LigaSure hemorrhoidectomy and the procedure for prolapse and hemorrhoids (PPH) are both relatively new treatments for managing symptomatic hemorrhoids. This review aimed to evaluate and compare their short-term outcomes. Methods: We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials and the China National Knowledge Infrastructure database for randomized controlled trials comparing the LigaSure procedure and PPH published in any lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…They found as an overall judgment, there was no difference between LigaSure and PPH techniques, but the recurrence rate was less in the LigaSure group. All in all, a previous meta-analysis that investigated the efficacy and safety of different techniques like conventional, LigaSure, stapled, Milligan-Morgan, as well as a harmonic scalpel and bipolar diathermy; have the same conclusions and recommendations, and are consistent with our findings [ 3 , 19 - 23 ].…”
Section: Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…They found as an overall judgment, there was no difference between LigaSure and PPH techniques, but the recurrence rate was less in the LigaSure group. All in all, a previous meta-analysis that investigated the efficacy and safety of different techniques like conventional, LigaSure, stapled, Milligan-Morgan, as well as a harmonic scalpel and bipolar diathermy; have the same conclusions and recommendations, and are consistent with our findings [ 3 , 19 - 23 ].…”
Section: Reviewsupporting
confidence: 90%
“…However, there is no difference between these techniques regarding the other outcomes like postoperative pain, bleeding, incontinence, and returned to normal activities. Also, Zhang and colleagues [ 23 ] conducted a systematic review and meta-analysis of trials that examine the difference between LigaSure hemorrhoidectomy and the procedure for prolapse and hemorrhoids (PPH) in postoperative pain, the rate of recurrence, returned to normal activities, and postoperative complications. They found as an overall judgment, there was no difference between LigaSure and PPH techniques, but the recurrence rate was less in the LigaSure group.…”
Section: Reviewmentioning
confidence: 99%
“…Based on the anal cushion descent theory, the procedure for PPH is designed to reposition and fix the descended cushions to their anatomical position, particularly in patients with Grade III and IV internal hemorrhoids. [19][20][21][22] Another minimally invasive technology, DG-HAL, has shown particular utility in treating Grade III and IV internal and mixed hemorrhoids. However, studies have indicated that PPH may result in long-term adverse effects, including high recurrence rates, rectal perforation, and pelvic abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, variations in the vasculature and muscular support of the anorectal region can predispose individuals to developing hemorrhoids. [4] Furthermore, microbial flora imbalances can contribute to localized inflammation, thereby exacerbating the condition. [5,6] Dietary habits, particularly a low intake of fiber and high consumption of processed foods, can lead to constipation, which is a significant risk factor for hemorrhoidal development.…”
Section: Introductionmentioning
confidence: 99%
“…Once LigaSure has achieved coagulation of the vascular structure, the electric current is automatically interrupted. With this limited spread of electric energy, LigaSure enables effective, bloodless hemorrhoid excision with minimal tissue damage [10,11].…”
Section: Introductionmentioning
confidence: 99%